Identification of E-Module (Book Creator) Utilization as a News Writing Learning Media to Support Public Transparency - Himmah, Ulil; Yusuf, Munawir; Darajati, Nur Arifah (Universitas Sebelas Maret, 2023)
In the digital era, E-modules have become one of the learning media used for news writing education. News writing is a language sk ill that aims to promote public transparency. The objectives of this research are (1) to identify the utilization of E-module (Book Creator) as a learning media for news writing to support public transparency, and (2) to understand the relationship between news and public transparency. Data collection techniques involved collecting relevant research findings from previous studies published in national and international journals. A total of 25 articles were selected as the objects of study, with 21 articles from national journals and 4 articles from international journals. The data analysis technique used was comparative narrative analysis. The research findings revealed that (1) the identification of E-module (Book Creator) utilization as a learning media for news writing to promote public transparency includes the following aspects: E - modules can assist the village's social media PIC (Person in Charge) in developing critical think ing skills, facilitating self-directed learning, encouraging interaction and active participation, as well as providing accessibility and affordability in learning. (2) News serves as a means of promoting public transparency. Based on the results of this study, the development of E-modules (Book Creator) as a learning media for news writing to promote public transparency in the village is necessary.